Pemikiran Tasawuf Syekh Ahmad Mutamakkin: Kajian Hermeneutik atas Naskah ‘Arsy Al-Muwahhidin - Islah Gusmian (Jurnal Lektur Keagamaan, 2013)
This paper explicates the sufistic thoughts of Syekh Mutamakkin in the text of ‘Arsy al-Muwahhidin, particularly  related to the main theme of salat which was viewed from both the fiqh and tasawuf perspective. Through his analysis, it was found that the Sufism foundation of Syekh Mutamakkin, essentially, was synthetical or hybridal form of both Islamic tradition and local (Javanesse) tradition. Consequently, the Muttamaqin sufism can not be doctrinarily classified whether into Sunni or Falsafi groups of Sufism, or neo-Sufism.Keywords: Syekh Mutamakkin, Tasawuf (Sufism), Salat (Praying), Serat Cebolek